Portfolio Concentration and Firm Performance - Ekholm, Anders; Maury, Benjamin (Journal of Financial and Quantitative Analysis, 2014)
Abstract This paper investigates the relation between shareholders’ portfolio concentration and firm performance. Using data on more than 1.3 million unique shareholders, we create an index that measures how concentrated shareholder portfolios are in each firm. We posit that portfolio concentration will affect incentives when shareholders are resource constrained. We find that average shareholder portfolio concentration is positively related to future operational performance and valuation. We also find that portfolio concentration is positively correlated with abnormal stock returns. Our findings suggest that shareholders with concentrated portfolios are more informed and play a governance role through the stock market.